Ethnobotanical Studies Medicinal Plants in Taulan Village, Regency Enrekang - Syamsiah, Syamsiah; Aulya, Rezky; Hiola, St. Fatmah; Abd. Muis (Bionature, 2024)
Ethnobotany is science that studies about utilization plant in a way traditional, one of them that is plant drugs. This study aims to determine types plant medicine and methods its use by village communities Taulan, Regency Enrekang. This research is of a nature descriptive explorative with method survey as well as technique interview to give detailed description of utilization plant medicine by the people in the village Taulan, Regency Enrekang. Method used is snowball sampling. Interview process done in an open-ended manner with guided by the table interview. Research result show as many as 53 types plants used by village communities Taulan as plant drug. Plant organs used​ like rhizomes, roots, stems, leaves, fruit, and flowers. Processing plant drug done with method simple, that is with method boiled, squeezed, chewed, or eaten direct as fresh vegetables.